2012
DOI: 10.1371/journal.pone.0046270
|View full text |Cite
|
Sign up to set email alerts
|

The Transcriptional Targets of Mutant FOXL2 in Granulosa Cell Tumours

Abstract: BackgroundDespite their distinct biology, granulosa cell tumours (GCTs) are treated the same as other ovarian tumours. Intriguingly, a recurring somatic mutation in the transcription factor Forkhead Box L2 (FOXL2) 402C>G has been found in nearly all GCTs examined. This investigation aims to identify the pathogenicity of mutant FOXL2 by studying its altered transcriptional targets.MethodsThe expression of mutant FOXL2 was reduced in the GCT cell line KGN, and wildtype and mutant FOXL2 were overexpressed in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
72
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 52 publications
2
72
0
Order By: Relevance
“…Computer modeling suggests that the presence of tryptophan does not disrupt the folding of the forkhead domain or its ability to interact with DNA, but that it may affect the interaction with other transcription factors (9). Actually, previous unbiased whole transcriptome analyses of GCT patient samples and cell lines indicated that FOXL2 with p.C134W mutation is unable to downregulate genes involved in the control of the cell cycle, and does not upregulate (as wild-type FOXL2) genes involved in cell death (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Computer modeling suggests that the presence of tryptophan does not disrupt the folding of the forkhead domain or its ability to interact with DNA, but that it may affect the interaction with other transcription factors (9). Actually, previous unbiased whole transcriptome analyses of GCT patient samples and cell lines indicated that FOXL2 with p.C134W mutation is unable to downregulate genes involved in the control of the cell cycle, and does not upregulate (as wild-type FOXL2) genes involved in cell death (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…A recurring somatic mutation in this gene has been described as a potential 'driver' in the pathogenesis of adult-type GCTs [7]. A few studies have investigated the effect of the mutant allele, including studying its transcriptional targets [8][9][10][11][12]. The identification of a recurring mutation reported to be present in up to 94-97% of adult-type tumours may serve as another diagnostic tool for GCTs, alongside traditional pathological and immunohistochemical features.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of this disease, it has been shown that this mutation alters the expression of different factors comprising aromatase Fleming et al, 2010;Kim et al, 2011;Rosario et al, 2012]; however, the mechanisms through which FOXL2 mutation induces these cancers remain a mystery.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, genes related to steroid production or signaling have been shown to be FOXL2 targets. StAR , CYP11A , CYP17A1, and HSD17B3 were described to be downregulated by FOXL2, limiting androgen production in the ovary [Pisarska et al, 2004;Park et al, 2010;Rosario et al, 2012;Elzaiat et al, 2014]. In contrast, a direct activating effect has been demonstrated on CYP19A1 , which favors female hormone synthesis through the conversion of androgens into estrogens [Pannetier et al, 2006;Fleming et al, 2010].…”
Section: Foxl2 Partners and Target Genesmentioning
confidence: 99%
See 1 more Smart Citation